Guiana dolphin movements across three decades between Sepetiba and Ilha Grande bays in southeastern Brazil - Daniel Anibolete Anibolete; Guilherme Maricato; Israel Maciel; Rodrigo Tardin (Ocean and Coastal Research)
Guiana dolphins in the Costa Verde estuarine complex of southeastern Brazil are relatively well-studied, but there is still limited knowledge about their movement patterns between the two management units in the region. This study was based on the identification of the individual dolphins that transited between the two Costa Verde management units. Dolphins were photo-identified within the study area from 1994 to 2020, and two photo-identification catalogs were compiled based on this material. These catalogs were systematically compared on the finFindR software, which found 80 individuals that had transited between both management units, between 904 in Sepetiba bay and 808 in Ilha Grande Bay. The most common type of movement was a one-way (no return) movement from Sepetiba to Ilha Grande bay (62.5 %).